MAGNETISM IN A FINELY DISPERSED SILICA-WATER SYSTEM - Kozlov A.N.; Skovorodkin Y.P.; Volosnev S.A.; Nekhoroshev A.V.; Sinel'nikova S.Y. (My University, 1987)
In laboratory experiments on the kinetics of magnetic properties in disperse systems the authors observed the production of magnetism in a silica-water system. Fine particle silica (quartz) with particle sizes from 400 to 50 μm was used. The paramagnetism and magnetic isotropy of the mixture were demonstrated experimentally by the overlap of the directions of the magnetic field induction vector of the earth and of the magnetization of the specimens and by the fact that the magnitude of this vector was independent of their orientation. Mixtures of such unsaturated organic components as acetone, ethanol and the like with silica had a positive magnetic susceptibility close to the k value of the silica-water mixture. But mixtures of these components with silica had practically the same diamagnetic susceptibility as the initial components. Additional aspects of the study are discussed.